2012
DOI: 10.5812/iranjradiol.7952
|View full text |Cite
|
Sign up to set email alerts
|

Skull Base Aneurysmal Bone Cyst Presented with Foramen Jugular Syndrome and Multi-Osseous Involvement

Abstract: Aneurysmal bone cyst (ABC) is an expansile bone lesion that usually involves the long bones. Skull base involvement is rare. Hereby, we describe a 17-year-old man with hoarseness, facial asymmetry, left sided sensorineural hearing loss and left jugular foramen syndrome. CT scan and MRI showed a skull base mass that was confirmed as ABC in histopathology. The case was unusual and interesting due to the clinical presentation of jugular foramen syndrome and radiological findings such as severe enhancement and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In some cases, the diagnosis of aneurysmal bone cyst is difficult because the radiological lesions are similar to other benign or malignant conditions, especially in unusual sites such as the base of the skull. 20,34 In the present case, an important differential diagnosis to be considered at the neurological examination would be hypothalamic-pituitary-axis lesions. However, the radiological aspect of the lesion was a massive cystic formation with a solid portion spontaneously denser than the cerebral parenchyma and sellar bone erosion, 35 not corresponding to the description of the neuroimaging aspect of most pituitary macroadenomas.…”
Section: Palavras-chavementioning
confidence: 78%
“…In some cases, the diagnosis of aneurysmal bone cyst is difficult because the radiological lesions are similar to other benign or malignant conditions, especially in unusual sites such as the base of the skull. 20,34 In the present case, an important differential diagnosis to be considered at the neurological examination would be hypothalamic-pituitary-axis lesions. However, the radiological aspect of the lesion was a massive cystic formation with a solid portion spontaneously denser than the cerebral parenchyma and sellar bone erosion, 35 not corresponding to the description of the neuroimaging aspect of most pituitary macroadenomas.…”
Section: Palavras-chavementioning
confidence: 78%
“…The associated bony pathology included fibrous dysplasia, chondroblastoma, osteoblastoma, nonossifying fibroma, and giant cell tumors. 2 It is postulated that the initiating process of the ABC is the microcyst, which forms as a result of intercellular edema in a primary lesion with loose, unsupported stroma. Rupture of vessels into the microcysts introduces blood under hemodynamic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Other lesions such as telangiectatic osteosarcoma, giant cell granuloma, and benign fibro-osseous lesions also have been reported to have similar multiple fluid level appearance on the MRI images. 1,2 Histologically, the lesion is characterized by the presence of multiple loculations, filled with venous blood and lined by spindle-shaped fibroblasts and with scattered multinucleated giant cells and stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal Bone Cyst of skull base is relatively rare and constitutes only 1% of cases. 2,3 Review of literature reveals that by far only 11 cases of ABC of clivus have been reported. 3 There are three phases in the development of aneurysmal bone cyst, namely 1.…”
Section: Discussionmentioning
confidence: 99%